The wine of wisdom : the life, poetry and philosophy of Omar Khayyam - Aminrazavi, Mehdi (Oneworld, 2005)
Representative of the exotic and erotic east, prophet of hedonism, champion of free thinkers, Omar Khayyam and his Ruba'iyyat have been the stuff of legend for centuries. This important work marks the first attempt to look at Khayyam's impact on the worlds of science, philosophy and poetry. Uniting a personal journey with scholarly ambition, Aminrazavi's work debunks the myths surrounding the legend to uncover the real Khayyam. From his extraordinary life, through his inspirational poetry, to his neglected philosophical and scientific writings and his considerable influenceon leading Western literary figures, including Mark Twain and T. S. Eliot, this is a unique journey into the heard and mind of the author of the Ruba'iyyat.